Trends in incidence, treatment, survival and subsequent breast cancer in lobular carcinoma in situ in the Netherlands: A population-based analysis. (October 2021) - van Maaren, Marissa C.; Ávila, Agustín Ortega; van Manen, Jeannette G.; Menke-Pluijmers, Marian BE.; Veltman, Jeroen; Bart, Joost; Westenend, Pieter J.; Siesling, Sabine
Abstract: Purpose: We analysed incidence, treatment, survival, occurrence of ductal carcinoma in situ (DCIS) and invasive breast cancer (IBC) after lobular carcinoma in situ (LCIS) in the Netherlands. Methods: All women diagnosed with classic LCIS between 1989 and 2017 were identified from the Netherlands Cancer Registry. We calculated overall (OS), relative survival (RS) and cumulative incidence functions (CIF, accounting for competing risks) of mortality, DCIS and IBC. For IBC, standardised incidence ratios (SIR) of IBC were calculated. Analyses were stratified for surgical treatment. Results: We included 1890 patients. Median age was 51 years. Median follow-up was 8.5 years. In 1989–2017, LCIS incidence increased from 41 to 124, surgical treatment decreased from 100% to 41.1 % – mostly BCS. 10-year OS and 20-year RS exceeded 90 % in all subgroups. Overall, 48 (2.5 %) and 270 (14.3 %) patients were diagnosed with DCIS and IBC. IBCs were mostly early-stage. After mastectomy, 13 of 14 IBCs presented contralaterally. In the other groups, 64.8–70.9 % of IBCs presented ipsilaterally, 34.5–53.9 % of these were lobular. The SIR of ipsilateral IBC was highest after no surgery (6.9, 95%CI:4.9–9.4), lowest after mastectomy (0.2, 95%CI:0.4–0.8). Conclusion: LCIS incidence increased, surgical treatment decreased. The low mortality risks support consideration of active surveillance. However, the increased IBC incidence suggests careful monitoring. Highlights: The incidence of LCIS increased, while surgical treatment decreased over time. 10- and 20-year relative survival rates exceeded 90 %, irrespective of surgery. The risk of breast cancer was highest after no surgery, lowest after mastectomy. Subsequent breast cancers were generally of low stage. Active surveillance for LCIS is advised, with the current follow-up five years.